Phytochemical Analysis and Antibacterial Activity of Ginger (Zingiber officinale) Methanolic Extract Against Escherichia coli and Staphylococcus aureus - Abdullahi, Nafi’atu; Zainab Isah; Haruna Saidu; Zainab Sabiya Salihu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Escherichia coli and Staphylococcus aureus are among the most prevalent pathogens found in food poisoning. Infections caused by these organisms are associated with high mortality rate in hospitalized patients. This study is aimed at evaluating the antibacterial activities of Ginger (Zingiberofficinale), Against Escherichia coli and Staphylococcus aureus using agar well diffusion method. Based on the phytochemical screening, the extract was tested for the presence of different chemical groups like Alkaloids, Flavonoids, Tanins, Steroids and Saponins. The result of this study revealed that the extract inhibited the growth of the microorganisms to varying proportion with zones of inhibition ranging from 7 to 16mm. The extract produced the highest zone of inhibition on Escherichia coli (16mm) while Staphylococcus aureus(14mm) shows the least. Furthermore, the phytochemical screening of the extract revealed the presence of Alkaloids, Flavonoids, Tanins, Steroids and Saponins in ginger. The presence of these phytochemical constituent in the extract could be responsible for the observed antimicrobial activity. The study confirms the use of Ginger extract in the treatment of wounds infection in the traditional medicine in different part of the world.